PENGARUH PENAMBAHAN ADITIF DAUN JAGUNG (Zea mays L.) TERHADAP SIFAT FISIS DAN MEKANIK KERAMIK ALUMINA - Ayu Dwi Retno; Ety Jumiati; Ridwan Yusuf Lubis (Universitas Riau, 2023)
Research has been carried out on the manufacture of alumina ceramics. This study aims to determine the effect of the addition of corn leaf additives on the physical and mechanical properties of alumina ceramics. Variations in the composition of alumina and corn leaf ash are: 95% : 5%; 90% : 10%; and 85% : 15%. The process of making these ceramics uses the die prissing method, and uses variations in firing temperature, namely 1300°C and 1400°C for 1 hour, and is printed using a 3 × 3 × 1 cm3 mold. the characterization of the tests carried out included physical properties, namely density and porosity and mechanical properties, namely hardness. The results of the data obtained from measuring the density at 1300°C are 2.11 – 2.18 g/cm3 and at 1400°C they are 2.13 – 2.20 g/cm3, the porosity at 1300°C is 25.82% – 27.25% and 1400°C temperature of 25.36% – 26.89%, and 1300°C temperature hardness test of 59.641 MPa – 67.055 MPa and 1400°C temperature of 61.926 MPa – 70.958 MPa.